EFFECTIVENESS OF DEVELOPMENT OF SEPSIS PREVENTION MODEL OF PATENTS TREATED IN WARD, PAK-CHOM HOSPITAL, LOEI PROVINCE - Thitithirarot, Thunyapat; Sirakan, Arunee; Piakhuanon, Piyawan (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2025)
The objective of this study was to develop a model for preventing bloodstream infections and to investigate the effects of the developed model on patients admitted to the inpatient department at Pakchom Hospital, Loei Province, Thailand. A mixed-methods research design was employed, consisting of six phases: 1) analyzing the nursing service situation for patients at risk of bloodstream infections in the inpatient department; 2) developing a model for preventing bloodstream infections; 3) piloting the developed model in the inpatient department; 4) evaluating and improving the model; 5) implementing the revised model; and 6) assessing the effectiveness of the model. The sample, selected through purposive sampling, included 36 patients admitted to the inpatient department and 32 staff members. Data were analyzed using descriptive statistics. The findings revealed that the developed model for preventing bloodstream infections comprised essential components, including an initial assessment and screening system for high-risk patients, continuous monitoring and evaluation, the use of clinical practice guidelines, ISBAR reporting to physicians, bedside supervision, and staff competency development. The implementation of the developed model reduced the incidence of bloodstream infections from 16.67% to 8.33%, and the staff expressed the highest level of satisfaction with the model. Therefore, this model for preventing bloodstream infections is beneficial and can be applied in nursing care for patients admitted to inpatient departments.